Liquid-gated field effect transistors based on single-walled carbon nanotubes : investigations of nanotubes-biomolecular interactions and ultra-sensitive biosensors - I Putu Mahendra Wijaya (2010)
Detection and analysis of biomolecules is of paramount importance in the areas of medical diagnostics, environmental monitoring and defense which often requires rapid, low-cost, portable, and high-sensitivity analysis. In this thesis, an alternative approach to attain these attributes is demonstrated by employing single-walled carbon nanotubes (SWCNTs) based liquid-gated field-effect transistor (LGFET) with an integrated microfluidic channel. To address the need for a simple and robust fabrication step, a simple lamination process is described in this thesis for the production of the device which requires merely two materials: SWCNTs and poly (dimethyl siloxane) (PDMS), an elastomer. This uncomplicated production process, which involves soft lithography, alleviates the need for photolithography altogether, besides the initial requirement of mold preparation. The integrated microfluidic channel offers advantages, such as: controlled delivery of the liquid sample, minute requirement of sample volume, and ability to perform kinetic measurements amongst others. The biomolecular interaction is then studied in real-time and label-free fashion within the aqueous liquid environment by monitoring the conductance of the semiconducting carbon nanotubes network. The size similarity of the nanotubes with most biomolecules and electronic properties of SWCNT derived from its hollow geometry renders the SWCNTs a potential candidate for high-sensitivity biosensing. To gain understanding about the interaction between the biomolecules and the nanotubes, a series of experiments have been performed to study the interaction between Bovine Serum Albumin (BSA) protein and the nanotubes, with a focus given to the reciprocal effect of such interactions: protein conformation change and conductance of the LGFETs. The carboxylated nanotubes inflicted a large conformational change in the protein than its pristine counterpart, thus, resulting in differential signal level in the transistor based kinetic measurement.This observation underscores the importance of the precise surface chemistry of the nanotubes in developing a biosensor. The application of SWCNTs LGFET in biosensing was investigated in the detection of 2, 4-dichlorophenoxy acetic acid (2, 4-D) herbicide in both buffer solution and soil extract by employing competitive immunoassay. The study suggests that the size of the bioanalytes determines the type of protocol that can be employed for the kinetic detection. Additionally, the experiment also highlights that lower ionic-strength solution, such as soil extracts, helps in signal amplification thus facilitating detection limits down to femto-molar concentrations. A similar ionic-strength dependency of the signal level is also found in the successive experiments of adsorption of poly (L-Lysine) (PLL) in different ionic-strength solutions.